Self-medication in Vietnam: Why do consumers purchase medicines without prescriptions? - Cuong Nguyen; Toan Do; Thuy Dang (Taylor & Francis Group, 2022)
Abstract: The research aims to establish the aspects that motivate individuals to buy medicines without prescription to self-medicate in Vietnam. A Health Belief Model diagram is used for the research, and a total of 426 valid answers are used for the data analysis. The outcomes prove that Perceived Threat, Perceived Benefits, Perceived Barriers, Perceived Self-efficacy and Modifying factors towards self-medication are the key reasons motivating individuals to buy medicine without prescription (self-medication) in Vietnam. The research shows several issues related to self-medication in Vietnam: Perceived Threat, Perceived Benefits, Perceived Barriers, and Perceived Self-efficacy.